Building National Cohesion and Domestic Legitimacy: A Regime Security Approach to Soft Power in China. (28th April 2015) - Edney, Kingsley
Abstract : Studies of Chinese soft power have emphasized its potential to ameliorate the security dilemma and help China achieve a 'peaceful rise'. While this perspective is useful, it overlooks an important alternative Chinese interpretation of soft power as a response to domestic security challenges. In order to address this omission, this article uses a regime security approach to examine soft power in the Chinese context. Through an investigation of the Chinese concept of 'cultural security' the article reveals that Chinese analysts view soft power as having the potential to help the Chinese Communist Party solve an internal security predicament by enhancing regime legitimacy and national cohesion.